Personal satellite services third international ICST Conference, PSATS 2011, Malaga, Spain, February 17-18, 2011, revised selected papers - Giambene, Giovanni 1966-; Sacchi, Claudio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International ICST Conference on Personal Satellite Services, PSATS 2011, held in Malaga, Spain, in February 2011. The 33 revised full papers presented were carefully reviewed and selected and cover a wide range of topics such as multimedia IP, next generation satellite networks, bandwidth allocation, aeronautic communications for air traffic management, DVB-S2, hybrid networks, delay tolerant networking, channel estimation and interference management, satellite antenna design, and localization systems.